1968
DOI: 10.1107/s0567739468000938
|View full text |Cite
|
Sign up to set email alerts
|

Periodic slip processes and the formation of polytypes in zinc sulphide crystals

Abstract: Inherent deformations of ZnS polytype regions are determined by measuring angles between linear markings. The deformations are correlated to the crystallographic structures of the polytypes as well. The relations clearly indicate that polytype formation occurred by a periodic slip process after crystal growth had been completed. Further observations substantiating this model are quoted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

1969
1969
1987
1987

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 4 publications
0
21
1
Order By: Relevance
“…The walls of the hollow tubes in different regions along the c axis of the specimen are found to be shear-deformed, with the shear perpendicular to the c axis in unison with the prismatic faces of the crystal. This effect is a direct consequence of the periodic-slip process and was discussed in detail in a former publication (Mardix, Kalman & Steinberger, 1968). The direction of the c axis in Fig.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The walls of the hollow tubes in different regions along the c axis of the specimen are found to be shear-deformed, with the shear perpendicular to the c axis in unison with the prismatic faces of the crystal. This effect is a direct consequence of the periodic-slip process and was discussed in detail in a former publication (Mardix, Kalman & Steinberger, 1968). The direction of the c axis in Fig.…”
Section: Methodsmentioning
confidence: 98%
“…The mechanism of the 'periodic-slip process" (Mardix, Kalman & Steinberger, 1968) of polytypic formation has by now a large volume of supporting experimental evidence (Alexander, Kalman, Mardix & Steinberger, 1970;Mardix, Lang & Blech, 1971). The same mechanism was found to be operative also in the formation of TiS polytypes (Legendre, Motet, Tronc & Huber, 1975;Legendre & Huber, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…To date the most detailed studies of polytypic phase transformations have been carried out for zinc sulphide (Secco d'Aragona, Delavignette & Amelinckx, 1966;Mardix & Steinberger, 1966;Mardix, Kalman & Steinberger, 1968) and cadmium iodide (Lal & Trigunayat, 1970;Tiwari & Srivastava, 1972). On the basis of these investigations, it is generally believed that the phase transformation in polytypic crystals occurs as a result of nucleation, propagation and rearrangement of stacking faults.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that in none of the crystals studied did any noticeable change in shape occur. This shows that the present transformations were not martensitic (Daniels, 1966;Mardix, Kalman & Steinberger, 1968). A local polytypic region, embodying a single partial dislocation ribbon and the accompanying stacking faults, was located by looking at thin crystals in an electron microscope under transmission and selecting an area exhibiting a single partial dislocation ribbon.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation